Tìm x: b ) 3 4 x X = 7 12
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: x*3/4=1/5
=>x=1/5:3/4=1/5*4/3=4/15
b: x*3/7=2/5
=>x=2/5:3/7=2/5*7/3=14/15
c: 1/3+2/9=2/12x
=>1/6x=3/9+2/9=5/9
=>x=5/9*6=30/9=10/3
d: 4/15*x-2/3=1/5
=>4/15*x=2/3+1/5=10/15+3/15=13/15
=>4x=13
=>x=13/4
e: x:1/7=2/3
=>x=2/3*1/7=2/21
f: 1/9:x=7/3
=>x=1/9:7/3=1/9*3/7=3/63=1/21
j: 1/4+5/12=8/3:x
=>8/3:x=3/12+5/12=8/12=2/3
=>x=4
h: =>7/4:x=1/5+1/2=7/10
=>x=7/4:7/10=10/4=5/2
thankkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkk
![](https://rs.olm.vn/images/avt/0.png?1311)
b: =>x(8-7)=-33
=>x=-33
c: =>-12x+60+21-7x=5
=>-19x=-76
hay x=4
d: =>-2x-2-x+5+2x=0
=>3-x=0
hay x=3
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) \(\dfrac{9}{20}-\dfrac{8}{15}\times\dfrac{5}{12}\)
\(=\dfrac{9}{20}-\dfrac{2}{9}\)
\(=\dfrac{41}{180}\)
b) \(\dfrac{2}{3}\div\dfrac{4}{5}\div\dfrac{7}{12}\)
\(=\dfrac{2}{3}\times\dfrac{5}{4}\times\dfrac{12}{7}\)
\(=\dfrac{5}{6}\times\dfrac{12}{7}\)
\(=\dfrac{10}{7}\)
c) \(\dfrac{7}{9}\times\dfrac{1}{3}+\dfrac{7}{9}\times\dfrac{2}{3}\)
\(=\dfrac{7}{9}\times\left(\dfrac{1}{3}+\dfrac{2}{3}\right)\)
\(=\dfrac{7}{9}\times1\)
\(=\dfrac{7}{9}\)
Bài 2:
a) \(2\times\left(x-1\right)=4026\)
\(\left(x-1\right)=4026\div2\)
\(x-1=2013\)
\(x=2014\)
Vậy: \(x=2014\)
b) \(x\times3,7+6,3\times x=320\)
\(x\times\left(3,7+6,3\right)=320\)
\(x\times10=320\)
\(x=320\div10\)
\(x=32\)
Vậy: \(x=32\)
c) \(0,25\times3< 3< 1,02\)
\(\Leftrightarrow0,75< 3< 1,02\) ( S )
=> \(0,75< 1,02< 3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
***c,4(x-5)-3(x+7)=-19
Suy ra (4x-20)-(3x+21)=-19
Suy ra (4x-3x)-(20+21)=-19
Suy ra x-41=-19
suy ra x=-19+41
Suy ra x=22
Vậy x=22
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,4.\left(x-5\right)-3.\left(x+7\right)=12\)
\(4x-20-3x-21=12\)
\(x-41=12\)
\(x=12+41\)
\(x=53\)
\(b,\left(x-4\right).\left(x-7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-4=0\\x-7=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=4\\x=7\end{cases}}\)
a) \(4\left(x-5\right)-3.\left(x+7\right)=12\)
\(4x-4.5-3x+3.7=12\)
\(4x-20-3x+21=12\)
\(4x-3x=12+20-21\)
\(x=12+20-21\)
\(x=32-21\)
\(x=11\)
Vậy \(x=11\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(-5\times\left(-x+7\right)-3\times\left(-x-5\right)=-4\times\left(12-x\right)+48\)
\(\Leftrightarrow5x-35+3x+15=-48+4x+48\)
\(\Leftrightarrow5x-3x+4x=35-15-48+48\)
\(\Leftrightarrow2x=20\)
\(\Leftrightarrow x=10\)
b ) \(-2\times\left(15-3x\right)-4\times\left(-7x+8\right)=-5-9\times\left(-2x+1\right)\)
\(\Leftrightarrow-30+6x-28x-32=-5+18x-9\)
\(\Leftrightarrow6x-28x-18x=30+32-5-9\)
\(\Leftrightarrow-40x=48\)
\(\Leftrightarrow x=-1.2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
− 12 . x = − 15 . − 4 − 12 − 12 . x = 60 − 12 − 12 . x = 48 x = 48 : − 12 x = − 4
b)
− 9 . x + 3 = − 2 . − 7 + 16 − 9 . x + 3 = 14 + 16 − 9 . x + 3 = 30 − 9 . x = 30 − 3 − 9 . x = 27 x = 27 : − 9 x = − 3
c)
− 12 . x − 34 = 2 − 12 . x = 2 + 34 − 12 . x = 36 x = 36 : − 12 x = − 3
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
− 12 . x = − 15 . − 4 − 12 − 12 . x = 60 − 12 − 12 . x = 48 x = 48 : − 12 x = − 4
b)
− 9 . x + 3 = − 2 . − 7 + 16 − 9 . x + 3 = 14 + 16 − 9 . x + 3 = 30 − 9 . x = 30 − 3 − 9 . x = 27 x = 27 : − 9 x = − 3
c)
− 12 . x − 34 = 2 − 12 . x = 2 + 34 − 12 . x = 36 x = 36 : − 12 x = − 3
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 12 : x = 3
X = 12 : 3
X = 4
b) 21 : x = 7
X = 21 : 7
X = 3
c) 30 : x = 3
X = 30 : 3
X = 10
d) X : 7 = 4
X = 4 x 7
X = 28
e) 20 : x = 5
X = 20 : 5
X = 4
f) X x 6 = 42
X = 42 : 6
X = 7